PyFrag 2019—Automating the exploration and analysis of reaction mechanisms - Sun, Xiaobo; Soini, Thomas M.; Poater, Jordi; Hamlin, Trevor A.; Bickelhaupt, F. Matthias (Journal of computational chemistry, 2019)
We present a substantial update to the PyFrag 2008 program, which was originally designed to perform a fragment‐based activation strain analysis along a provided potential energy surface. The original PyFrag 2008 workflow facilitated the characterization of reaction mechanisms in terms of the intrinsic properties, such as strain and interaction, of the reactants. The new PyFrag 2019 program has automated and reduced the time‐consuming and laborious task of setting up, running, analyzing, and visualizing computational data from reaction mechanism studies to a single job. PyFrag 2019 resolves three main challenges associated with the automated computational exploration of reaction mechanisms: it (1) computes the reaction path by carrying out multiple parallel calculations using initial coordinates provided by the user; (2) monitors the entire workflow process; and (3) tabulates and visualizes the final data in a clear way. The activation strain and canonical energy decomposition results that are generated relate the characteristics of the reaction profile in terms of intrinsic properties (strain, interaction, orbital overlaps, orbital energies, populations) of the reactant species. © 2019 The Authors. Journal of Computational Chemistry published by Wiley Periodicals, Inc. PyFrag 2019 is a user‐friendly python program that resolves three main challenges associated with the automatized computational exploration of reaction mechanisms: (1) the management of multiple parallel calculations to automatically find a reaction path; (2) the real‐time monitoring of the entire computational process; and (3) the analysis and presentation of these data in a clear and informative way to rationalize the characteristics of the reaction profile in terms of intrinsic properties of the reactant species by means of the activation strain model (ASM) and an energy decomposition analysis (EDA, when using ADF).